2018
DOI: 10.3340/jkns.2017.0404.013
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of Sagittal Balance in Spinal Deformity Surgery

Abstract: The prevalence of patients with adult spinal deformity (ASD) has been reported as high as 68%. ASD often leads to significant pain and disability. Recent emphasis has been placed on sagittal plane balance and restoring normal sagittal alignment with regards to the three dimensional deformity of ASD. Optimal sagittal alignment has been known to increase spinal biomechanical efficiency, reduce energy expenditure by maintaining a stable posture with improved load absorption, influence better bony union, and help … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(61 citation statements)
references
References 52 publications
(98 reference statements)
1
55
0
5
Order By: Relevance
“…Approximately the same kyphosis and lordosis curve reductions for CAD-FEM and conventional braces have been reported [46,51,53] (Table 4), whereas CAD-FEM braces reportedly are more effective than CAD-CAM braces from this point of view (group 4) [55] (Table 5). It has been shown that CAD-FEM and conventional braces (group 3) improved sagittal balance [61] equally [46] ( Table 4). Overall, several studies have obtained equivalent effectiveness for CAD-CAM, CAD-FEM, and conventional braces.…”
Section: Sagittal Plane Kyphosis Lordosis and Sagittal Balancementioning
confidence: 95%
“…Approximately the same kyphosis and lordosis curve reductions for CAD-FEM and conventional braces have been reported [46,51,53] (Table 4), whereas CAD-FEM braces reportedly are more effective than CAD-CAM braces from this point of view (group 4) [55] (Table 5). It has been shown that CAD-FEM and conventional braces (group 3) improved sagittal balance [61] equally [46] ( Table 4). Overall, several studies have obtained equivalent effectiveness for CAD-CAM, CAD-FEM, and conventional braces.…”
Section: Sagittal Plane Kyphosis Lordosis and Sagittal Balancementioning
confidence: 95%
“…Во всех случаях применялись титановые стержни диаметром 6 мм (n = 35) и 5,5 мм (n = 12). Технически субтракционная педикулярная остеотомия выполнялась по стандартной методике, описанной в литературе [7,8]. Однако на этапе смыкания сформировавшегося дефекта вначале устанавливались короткие стержни, охватывающие только зону остеотомии и смежные сегменты, с постепенной попеременной их контракцией.…”
Section: материал и методыunclassified
“…Применение корригирующих остеотомий позвоночника для коррекции сагиттального баланса в течение последних двух десятилетий приобрело широкое распространение. В зависимости от ригидности и степени деформации позвоночника в сагиттальной плоскости применяются остеотомии задней колонны (остеотомии по Ponte и Smith-Petersen) и трехколонные остеотомии -педикулярная субтракционная остеотомия (pedicle subtraction osteotomy -PSO) и резекция позвоночного столба (vertebral column resection -VCR) [1][2][3][4][5][6][7].…”
Section: Introductionunclassified
See 2 more Smart Citations